(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2023)
This article is devoted to the use of digital tools in the language education of Russian philology students during practical Russian language classes. The publication is based on the author’s experience in the implementation of the author’s game „Decode Matryoshka” using QR codes and the use of information and communication technology resources to create her own teaching materials, e.g. quizzes created using online tools: Kahoot and Quizlett that allow you to personalize teaching tasks.